ANALISIS STRATEGI PEMASARAN PADA PELAYANAN OPERASI PENGGANTIAN SENDI LUTUT - Maryani, Nining Tri; Adi, Ni Putu Deni (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2021)
Total knee replacement is a safe treatment to reduce pain and restore physical function in patients with severe osteoarthritis that cannot be treated with physical therapy. Every year there are more than 500,000 total knee replacement surgical procedures performed in the United States, it is estimated that by 2030 the volume of TKR surgical procedures will increase to more than 3.48 million per year due to premature aging and increasing obesity. With the opportunity for demand from the TKR service itself, the Karima Utama Special Surgery Hospital feels the need to establish a marketing strategy for knee joint replacement surgery services. This article was built as a descriptive research with a qualitative approach. The place of research was carried out at the Karima Utama Special Surgery Hospital and the instrument used was an interview guide. The results and conclusions of the research carried out are the marketing mix of joint replacement surgery services is the product mix is post surgery with minimal pain and implementation of excellent service according to standards, price mix by making price packages, place mix by picking up patients from out of town and abroad, promotion mix, with leaflets, public education, public seminars, health facilities 1 seminar, social media, educational radio and TV media.